THE CONTRIBUTIONS OF ACTIVIN B SIGNALING TO DIABETIC KIDNEY DISEASE - Khajehei, Mohammad (My University, 2022)
DKD is the leading cause of kidney failure in Canada and its patients suffer the highest morbidity and mortality rates of any kidney failure patient group. Current interventions including strict glycemic control only delay DKD. Thus, there is a major need to identify new therapeutic targets. High glucose (HG) is identified as a major pathogenic factor, inducing the release of growth factors leading to kidney fibrosis. Although treatments have been developed to target these factors, their effectiveness is accompanied by adverse effects due to the lack of specificity. Recently, activins have been suggested to have a prominent role in promoting renal fibrosis and developing a specific anti-activin therapy can avoid potential side effects. Although there is evidence supporting an important role for activin A (ActA) in the induction of fibrosis in DKD, whether ActB also contributes is unknown. In this study, we aim to determine the potential contribution of ActB to promoting fibrosis. Our results show that ActA and ActB are upregulated in rodent and human DKD. We show that hyperglycemia leads to the secretion of ActA and ActB by mesangial cells (MC), whereas only ActB is secreted by renal fibroblasts (RF). Similar to HG, treatment with ActA or ActB leads to Smad2/3 activation and upregulation of extracellular matrix proteins, whereas specific inhibition of either ActA or ActB attenuates these effects. We show that ActA and ActB regulate HG-induced activation of MRTF-A/SRF in MC, leading to an activated phenotype characterized by increased α-SMA expression and ECM production. Lastly, we confirm the specificity and functionality of the activin propeptides in vitro, providing evidence for their effectiveness in vivo. This study will help further our knowledge of the role activins in DKD, potentially providing an alternative therapy.
ACTIVIN B IN DIABETIC KIDNEY DISEASE
Keywords: diabetic kidney disease; activin B